(untitled) (American Journal of Islam and Society, 2015)
In this challenging and thought-provoking monograph, Ahmad Atif Ahmad draws on the issue of futūr al-Sharī‘a (the end of access to divine guidance due to the absence of qualified jurists) to explore how early Muslim scholars debated its possible loss. Basing himself upon the analysis of medieval Sunni legal and theological texts, the author divides his monograph into four parts: Part I, “Foundations,” chapters 1-3; Part II, “Jurists and Nonjurists,” chapters 4-6; Part III, “Modernity and Its Questions,” chapters 7-8; and Part IV, “Beyond Modernity,” chapters 9-10. Ahmad situates his project as a commentary on the debate over the destiny of religious teachings “from the point of view of Muslim jurist-theologians and those who engaged the intellectual production of these jurists and theologians” (p. 1). He pursues his central goal, to explore “the destiny and current status of God’s guidance from a Muslim perspective” (p. 2), by explaining that medieval Muslim theologians and jurists defined the Shari‘a’s survival in terms of the availability of scholarly “knowledge” about it (p. 2). Utilizing these medieval debates to offer important insights into similar contemporary debates, he insists that empirical research will continue to refute the “death of the sharī‘a” thesis. In the Introduction, Ahmad poses a question that goes to the heart of this debate: Could God’s guidance, available to previous generations as religious histories tell us, somehow become inaccessible at some point? His premise is that the “fatigue of the sharī‘a” has been a subject of continuous debate throughout the Islamic tradition and thus cannot be considered a “recent” or “modern” phenomenon. He closely evaluates two kinds of debates: (1) those in the Islamic tradition about the end of access to futūr al-Sharī‘a and (2) those in modern western scholarship in the discipline of Islamic legal studies about the Shari‘a’s death. One of the important issues in this book is Ahmad’s discussion of this supposed “fatigue” in relation to other intertwined inquiries about the nature of ijtihād (independent reasoning), God’s guidance and justice, and the availability of His guidance today (p. 15). This suggests to the reader that the claims made about this fatigue can be answered only after addressing auxiliary, yet fundamental, concerns about the Shari‘a in Muslim societies. Ahmad further complicates the question of its death by pointing out the medieval relationship between legal and theological reflections on this question. He alerts readers to the problem of defining “sharī‘a” and “fatigue of the sharī‘a” and observes ...